2013
DOI: 10.1017/s1751731112001449
|View full text |Cite
|
Sign up to set email alerts
|

Stress responses to comparative handling procedures in sheep

Abstract: The objective of this study was to compare some husbandry procedures on the base of physiological stress parameters and evaluate the welfare status in sheep. Forty ewes were used as the study material. Measurements were taken during several routine husbandry procedures such as milking, shearing, weighing, loading and hoof care. Data regarding time spent for each application, as well as heart and respiratory rates were recorded during the applications. Blood samples were taken 15 min before and after each appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…3). Yardimci et al (2013) recently showed in sheep that handling associated with weighing decreases reduced GSH concentrations in blood, which could explain the decrease in GSH concentrations in control lambs (Fig. 3).…”
Section: Resultsmentioning
confidence: 85%
“…3). Yardimci et al (2013) recently showed in sheep that handling associated with weighing decreases reduced GSH concentrations in blood, which could explain the decrease in GSH concentrations in control lambs (Fig. 3).…”
Section: Resultsmentioning
confidence: 85%
“…hand or machine milking), can markedly affect the welfare, health and production performance of dairy sheep. Although the use of the milking machine belonging to the modern farming systems determines a reduction in the animal handling and, consequently, a decrease in stress (Yardimci et al, 2013), the milking rooms show some critical points that can be a source of stress. Under stressful stimuli the body must find a new dynamic equilibrium, and this requires several adaptive body responses.…”
Section: Discussionmentioning
confidence: 99%
“…The transition to modern farming systems can impose severe restrictions on the space available for dairy sheep. The use of the milking machine belongs to the modern farming systems and it determines a reduction in the animals handling and, consequently, a decrease in stress (Yardimci et al, 2013). However, the milking rooms show some critical points that can be a source of stress.…”
Section: Introductionmentioning
confidence: 99%
“…The stress generated by shearing has several components: the movement of animals to the pens, noises and movements related to shearing of other animals, handling and restraint during shearing in an unknown environment, and shearing itself (63) . In addition, it also adds thermal stress generated by the loss of the naturally insulating layer of wool, especially when it is done in winter (64) . The stress response is similar in sheep sheared by hand or with a shearing machine (65) .…”
Section: Prepartum Shearing In Sheepmentioning
confidence: 99%
“…El estrés generado por la esquila tiene varios componentes: el movimiento de los animales al corral, ruidos y movimientos vinculados a la esquila de los otros animales, manipulación e inmovilización durante la esquila en un entorno desconocido y la esquila en sí misma (63) . Por otro lado, también se suma el estrés térmico generado por la pérdida de la capa naturalmente aislante del ovino, especialmente cuando se realiza en invierno (64) . La respuesta de estrés es similar en ovejas esquiladas a mano o con máquina de esquilar (65) .…”
Section: Esquila Preparto En Ovinosunclassified